A Sorocaba das Batalhas: ocupações juvenis de espaços públicos na cidade - França, Wellington dos Santos (2020)
This essay aims to analyse the processes of the suburb expanding and the unequal urban development in Sorocaba city whithin its historical context, taking into account industrial expansion happened in the city in 70’s and 80’s as well as the real state speculation strenghtening in the 90’s. In addition, it aims to comprehend the youthful culture practices of occupation and re-signification of the public space through hip-hop culture. Based in an ethnografic method, the essay searched highlightening the rhyme battles reality in Sorocaba, in order to comprehend the dynamics and the developed relations by arising youths from suburb about to set a new way of moving around and experiencing urban spaces, through the struggle for the right to the city.